Rancang Bangun Aplikasi Analisis Kelayakan Pendirian Indomaret Dengan Metode Analytical Hierarcy Process Dan Graphic Rating Scale Pada CV. Sigma Sukses Kreasi - Darmanto, I Made Budi; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Sigma Sukses Kreasi is a consulting business services that will conduct socio-economic studies to determine the feasibility of Indomaret establishment. But, in practice there are many problems. In the data processing is still very slow, moreover the analysis process of determining a recommendation of feasibility is still speculative, accordingly the result of recommendations are not comprehensive and consistent.So that, it requires an application with the calculation method that can improve the analysis process of determining the feasibility of Indomaret establishment. Analytical Hierarchy Process (AHP) methods is used to define weights of feasibility criteria. And then, the weights of feasibility criteria will be used in the questionnaire data assessment that used the Graphic Rating Scale (GRS) for resulting the value of the feasibility of Indomaret establishment.According to the trial results, this application can determine the feasibility of Indomaret establishment, particularly in the case study at Indomaret Dharmawangsa. In addition, based on the trial results, this application can help the data processing to be faster, and the analysis process of determining the recommendations of feasibility of Indomaret establishment become more comprehensive and consistent.